STRATEGI PEMASARAN SYARIAH PADA UMKM KULINER - Zainur Ridho; Abdul Mannan (IZZI: Jurnal Ekonomi Islam, 2023)
This study aims to analyze the Islamic marketing strategy applied in the culinary MSME "Mie Pangsit" owned by Mr. H. Wahet in Randumerak Village, Paiton District, Probolinggo Regency. Using a descriptive qualitative approach, this research explores marketing practices, business management, and the implementation of Islamic business values in the daily operations of the enterprise. The findings reveal that the Islamic marketing strategy is reflected through honesty in transactions, responsibility for product quality, affordable pricing, and fair service delivery. The owner consistently practices spiritual values such as charity, almsgiving, and zakat, which contribute to the sustainability and blessing of the business. The implementation of Islamic business principles—such as honesty (sidq), trustworthiness (amanah), justice (‘adl), and benevolence (ihsan)—has strengthened consumer trust and improved long-term business resilience. The study concludes that integrating syariah values into marketing management can serve as an effective strategy to enhance the competitiveness of traditional culinary MSMEs.